2019
DOI: 10.21037/gs.2019.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Does multiparametric US improve diagnostic accuracy in the characterization of small testicular masses?

Abstract: Background: Recent advances in ultrasonography (US) have produced new innovative techniques for the non-invasive assessment of testicular masses. The aim of this study was to investigate the diagnostic performance of multiparametric US, including gray-scale, Color-power Doppler and real-time elastography (RTE) analysis, in the characterization of testicular lesions.Methods: Fifty-four patients (median 42.2 years; range, 10-64 years) with testicular lesions detected with gray-scale US and power Doppler US were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
2
31
0
1
Order By: Relevance
“…A sensitivity analysis was also performed, with the results showing significant heterogeneity for the studies by Goddi et al [ 21 ] and Reginelli et al [ 25 ] ( Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A sensitivity analysis was also performed, with the results showing significant heterogeneity for the studies by Goddi et al [ 21 ] and Reginelli et al [ 25 ] ( Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-regression and subgroup analyses showed that neither the study design nor the interpretation method had a significant impact on the diagnostic accuracy nor the heterogeneity of studies. The sensitivity analysis showed that the studies by Goddi et al [ 21 ] and Reginelli et al [ 25 ] had significant heterogeneity, potentially due to differences in ultrasound scanning equipment or the histological diversity of lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Az UH-vizsgálat elegendő lehet a kezelési terv felállításához, ugyanakkor a pontos diagnózishoz nem mindig elegendő. A multiparametrikus UH-vizsgálat, elasztográfiás módszerrel, talán még megbízhatóbb diagnózissal szolgálna a here elváltozásainak esetében [8,9], de ez a módszer nem áll rendelkezésünkre. Tapasztalataink alapján (lásd harmadik beteg) a magasabb rendű képalkotó vizsgálat (MR) elvégzése sem volt elegendő a pontos diagnózis felállításához, a terápiás tervet viszont nem módosította, csak annak megtervezésében volt segítségünkre.…”
Section: Esetismertetésunclassified